2013
DOI: 10.1179/1743132813y.0000000166
|View full text |Cite
|
Sign up to set email alerts
|

Evolving management of symptomatic chronic subdural hematoma: experience of a single institution and review of the literature

Abstract: Objective-Chronic subdural hematoma has an increasing incidence and results in high morbidity and mortality. We review here the ten-year experience of a single institution and the literature regarding the treatment and major associations of chronic subdural hematoma (cSDH).Methods-We retrospectively reviewed all cSDHs surgically treated from 2000 to 2010 at our institution to evaluate duration from admission to treatment, type of treatment, length of stay in critical care, length of stay in the hospital and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 81 publications
(82 reference statements)
0
32
1
3
Order By: Relevance
“…10 The study by Balser et al was the only study to examine the logistical and economic implications and concluded that the new minimally invasive techniques have many benefits over BHC including shorter time to intervention, length of hospital stay, and overall cost of treatment. 2 These findings highlight the many benefits of SEPS/ hollow screw over traditional techniques. First, the minimally invasive nature of these techniques means that they can be performed after administration of a local anesthetic at the bedside.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…10 The study by Balser et al was the only study to examine the logistical and economic implications and concluded that the new minimally invasive techniques have many benefits over BHC including shorter time to intervention, length of hospital stay, and overall cost of treatment. 2 These findings highlight the many benefits of SEPS/ hollow screw over traditional techniques. First, the minimally invasive nature of these techniques means that they can be performed after administration of a local anesthetic at the bedside.…”
Section: Discussionmentioning
confidence: 92%
“…2 All studies concluded that the new techniques are safe and effective procedures and should be considered in the treatment of CSDH, while 2 studies concluded that they should be first-line techniques. 9,12 The 3 case-control studies all concluded that while minimally invasive hollow screw techniques were an established alternative, superiority had not been proven and more evidence was needed to establish these techniques as superior to traditional ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os HSDCr constituem apresentação comum de hemorragia intracraniana. Estão associados comumente a traumatismos cranioencefálicos prévios, geralmente de leve intensidade, com taxas de morbidade e mortalidade relativamente altas (1)(2) , ocorrendo principalmente em idosos. Outra lesão que se assemelha ao HSDCr é o Higroma Subdural, sendo que a distinção entre ambos permanece controversa.…”
Section: Introductionunclassified
“…Haja vista o progressivo envelhecimento da população mundial observa-se, atualmente, aumento na incidência das coleções subdurais crônicas. Isso promove maior impacto na qualidade de vida do indivíduo, refletindo em custos tanto sociais quanto econômicos para as populações envolvidas (2) . O processo de atrofia cerebral constitui fator de risco significativo associado principalmente aos idosos e etilistas crônicos.…”
Section: Introductionunclassified